2005
DOI: 10.1253/circj.69.1022
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Distal Left Anterior Descending Artery Flow Velocity by Transthoracic Doppler Echocardiography and Corrected TIMI Frame Count Before Mechanical Reperfusion in Patients With Anterior Acute Myocardial Infarction

Abstract: uick and accurate evaluation of coronary reperfusion in patients with acute myocardial infarction (AMI) is essential to determine whether thrombolysis and/or percutaneous coronary intervention (PCI) is required to achieve reperfusion. [1][2][3][4][5][6][7] Recent advancements in transthoracic Doppler echocardiography (TTDE) have enabled direct visualization and evaluation of coronary blood flow velocity, especially in the distal left anterior descending coronary artery (LAD). [8][9][10][11][12][13][14][15][16]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…More recently, in a preliminary study on EECP and CSF, we showed that coronary flow indices by TTDE correlated well with angiographic estimation of coronary flow [12]. The present study demonstrated that there was an excellent inverse correlation between resting DPFV and TFC for LAD (r = –0.821, p < 0.001), and CFR was inversely correlated with the mean TFC (r = –0.549, p < 0.001), which is consistent with our previous report and the results reported by Lee et al [18] and Caliskan et al [19]. These results suggested that CFV and CFR measured by TTDE could be reliable indices for assessing coronary flow in patients with CSF.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…More recently, in a preliminary study on EECP and CSF, we showed that coronary flow indices by TTDE correlated well with angiographic estimation of coronary flow [12]. The present study demonstrated that there was an excellent inverse correlation between resting DPFV and TFC for LAD (r = –0.821, p < 0.001), and CFR was inversely correlated with the mean TFC (r = –0.549, p < 0.001), which is consistent with our previous report and the results reported by Lee et al [18] and Caliskan et al [19]. These results suggested that CFV and CFR measured by TTDE could be reliable indices for assessing coronary flow in patients with CSF.…”
Section: Discussionsupporting
confidence: 92%
“…In these patients, coronary blood flow has often been quantitatively evaluated by TFC on coronary angiography [1,13,14], which is invasive and expensive, limiting its use in the clinical setting. TTDE is a noninvasive, relatively inexpensive and widely used method for measuring CFV and CFR in the distal LAD [18,19,20]. To our knowledge, however, the correlations between CFV measured by TTDE and angiographic TFC have not been fully elucidated in patients with CSF, although in a previous study in patients with anterior acute myocardial infarction before mechanical reperfusion [18], DPFV of the distal LAD by TTDE showed a significant correlation with corrected TFC by angiography (r = –0.74, p < 0.001), and Caliskan et al [19] reported a strong inverse correlation between TFC and CFR in patients with CSF (r = –0.62, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CTFC method yields results that are concordant with other diagnostic modalities including transthoracic Doppler echocardiography (TTDE), single photon emission computerized tomography (SPECT), magnetic resonance imaging (MRI), intravascular ultrasound (IVUS) and intracoronary Doppler and pressure measurements [29][30][31][32]. Diastolic peak velocity of the distal LAD flow measured by pulsed TTDE has demonstrated a significant correlation with the CTFC (r = -0.74, P \ 0.001).…”
Section: Concordance Between the Ctfc And Other Imaging Modalitiesmentioning
confidence: 74%
“…Recently, the transthoracic Doppler echocardiography (TTDE) technique has emerged to take reliable measurements of the CFV and CFV reserve (CFVR) in the left anterior descending artery (LAD) using intravenous administration of adenosine 5'-triphosphate (ATP). [7][8][9] Accordingly, we evaluated the usefulness of TTDE for the non-invasive assessment of the coronary arterial tone in human LAD.…”
mentioning
confidence: 99%